The impact of TTIP: the underlying economic model and comparisons - Pelkmans, Jacques; Lejour, Arjan M.; Schrefler, Lorna; Mustilli, Federica; Timini, Jacopo (Brussels, 2014)
"What are the economic and other impacts of the Transatlantic Trade and Investment Partnership? At the request of the European Parliament, CEPS has provided an appraisal of the TTIP Impact Assessment carried out by the European Commission, with special elaboration of the underlying economic model. The methodology applied by the Centre for Economic Policy Research (CEPR) for this economic modelling is analysed in depth, together with the assumptions used to make TTIP amenable to an economic appraisal. The research paper also compares the IA on TTIP with selected previous empirical economic assessments of EU trade agreements and with a set of alternative studies on TTIP itself. In reading our findings, two central caveats should be kept in mind that affect any analysis of the CGE model included in the European Commission’s Impact Assessment. First, TTIP is a rather unusual bilateral trade agreement; and second, TTIP is so wide-ranging that an alternative approach, such as the so-called ‘partial’ (equilibrium) approach – already a second-best solution – would be totally inappropriate to the case under examination.